Physically upgrading crude palm oil by reducing free fatty acid content through glycerolysis chemical reaction in the deacidification process via ultrasonic probe atomisation / Nurul Liyana Rosli - Rosli, Nurul Liyana (2024)
CPO is useful for a wide range of applications, from food to cosmetics and industrial products as well as feedstock for biodiesel production, but not without its drawbacks. One of the main concerns with CPO is FFA content, which naturally present in CPO that can cause the oil to become rancid and lead to a decrease in product quality. FFA content in CPO can also corrode machinery and cause safety issues when it is used in the production of biodiesel. There are several technologies that can be used to reduce FFA content in CPO. These include physical refining, chemical refining, and enzymatic refining. One of the alternatives for CPO upgrading to reduce FFA content is UPA. However, there is no research reported on the GCR via UPA. This method allows for more efficient reduction of FFA content in the CPO, resulting in a higher-quality product and fewer safety concerns. GCR via UPA is a novel way that improve understanding in the research area. The first objective of the research is to evaluate the CPO physicochemical and quality characteristics using GC of methyl esters, WijsTitrimetry, spectrophotometry, open-ended capillary tube, and Pycnometry prior to GCR via UPA. The modified method of AOCS Official Method Ce 1h‑05 was used for the first objective. The second objective of the research is to analyse the CPO reaction using FlatMol 2 Lite software to predict the mechanism and to determine the mass of glycerol for the GCR via UPA. The canvas method was used for the second objective. The third objective of the research is to investigate the GCR via UPA where the independent variables are method (with and without UPA) and solvent (with and without glycerol) while the dependent variables are FFA content and DPO yield. The OFAT method was used for the third objective. The fourth objective of the research is to determine the CPO modeling for the equation model for GCR via UPA using DesignExpert software. The RSM was used for the fourth objective. All findings in the evaluation of the CPO characteristics meet the recommended value, which indicates that the CPO has good characteristics. The outcome of the analysis of the CPO reaction shows that the FFA content in the CPO is increasing when a hydrolysis chemical reaction occurs and decreasing when a GCR occurs. The research also discovered that the suitable mass ratio of glycerol to CPO in the GCR in the DP via UPA is 24:200. The discoveries made during the investigation of the CPO upgrading reveal that the GCR via UPA is a worthwhile process as it may reduce the FFA content in the CPO while minimising the processing time, energy, and operating costs. The results of the determination of the CPO modeling show that both models of FFA content and DPO yield were valid and can be used to re-establish the future results GCR via UPA. Generally, the research shows that the GCR in the DP using UPA is sustainable and should be utilised for CPO upgrading to reduce FFA content in DPO production.